Consumers Protection Who Buy Products Through Instagram: A Comparative Study of Indonesia and Singapore - Chairunnisa Yumna Risti; Ridha Wahyuni (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The purpose of this study is to analyze and compare the protection of consumers who purchase products through the Instagram media platform in Singapore and Indonesia. The laws governing consumer protection and electronic transactions in both countries are examined in this study, which uses a normative legislative and comparative juridical approach. The study shows that Indonesia has two laws: Consumer Protection Act (UUPK) and Electronic Information and Transaction Act (UU ITE), but their implementation has not been optimal in protecting consumers from fraud, default, and other legal issues. Meanwhile, Singapore has a Consumer Protection (Fair Trading) Act 2003 (CPFTA) and a CaseTrust program that are more effective in providing protection and increasing consumer confidence. This research observes that Indonesia needs to learn from Singapore's practices, such as the awarding of the Trustmark logo, to enhance consumer protection that is more effective and adaptive to technological developments and phenomena in society. This research is expected to provide dedication related to the development of better consumer protection against technological developments and phenomena in society